da Silva Oliveira - Pozzi de Moraes Campos, Ayandara; Belo de Jesus, Thamires (LINKSCIENCEPLACE, 2026)
This investigative class report aimed to revise concepts of flat geometry with emphasis on teaching the sum of the internal angles of a convex polygon, through the construction of a paper boat. The activity was developed with students of the 2nd year of the Technical Course in Integrated Administration at the High School of the Federal Institute of Education Science and Technology of Espírito Santo, during acting as substitute teacher in the Cariacica Campus. We developed construction and planning of the paper boat and through the investigation the students were being led by means of questions and discussions for the deduction of the formula of the sum of the internal angles. The results show that the students recognized patterns and abstracted, being possible to generalize the sum of the internal angles of a convex polygon of n sides through the mediated construction.